2005
DOI: 10.1074/jbc.m412009200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Purified 5-HT4 Receptor

Abstract: Serotonin 5-HT 4(a) receptor, a G-protein-coupled receptor (GPCR), was produced as a functional isolated protein using Escherichia coli as an expression system. The isolated receptor was characterized at the molecular level by circular dichroism (CD) and steady-state fluorescence. A specific change in the near-UV CD band associated with the GPCR disulfide bond connecting the third transmembrane domain to the second extracellular loop (e2) was observed upon agonist binding to the purified receptor. This is a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
127
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 137 publications
(137 citation statements)
references
References 32 publications
9
127
0
1
Order By: Relevance
“…Mutation of Cys 279 (6.47) to Ala or Tyr (a mutation causing infertility in man) and Asn 315 (7.45) to Ala increases ligand binding affinity for GnRHs from other species and converts them to full agonists [76]. Recent studies have shown that partial agonists stabilize a receptor active conformation differing from that of full agonists, with different signaling capability [6,109]. Taken together these findings suggest that a complex receptor intramolecular interaction network evolved during evolution for selective binding of ligands and G protein activation.…”
Section: Differential Gnrh Receptor Conformations Dictate Different Lmentioning
confidence: 99%
“…Mutation of Cys 279 (6.47) to Ala or Tyr (a mutation causing infertility in man) and Asn 315 (7.45) to Ala increases ligand binding affinity for GnRHs from other species and converts them to full agonists [76]. Recent studies have shown that partial agonists stabilize a receptor active conformation differing from that of full agonists, with different signaling capability [6,109]. Taken together these findings suggest that a complex receptor intramolecular interaction network evolved during evolution for selective binding of ligands and G protein activation.…”
Section: Differential Gnrh Receptor Conformations Dictate Different Lmentioning
confidence: 99%
“…The most detailed description of the conformational repertoire that a GPCR can adopt has been obtained in the case of the β 2 -adrenergic receptor with an experimental demonstration of a complex conformational landscape where ligands with distinct pharmacological properties shift the conformation of the receptor from one state to another (4)(5)(6)(7)(8)(9)(10)(11). In the same way, we showed that ligands with different efficacies stabilize different conformations of the serotonin receptor (12). Despite this wealth of data, understanding of GPCR activation mechanisms, and in particular of the necessary influence of signaling proteins on the receptor conformational repertoire, is still incomplete.…”
mentioning
confidence: 91%
“…In general, the receptor transmembrane helices (TMs) rearrange, allowing the intracellular loop region to unfold and to stimulate neighboring G proteins (3,4). Conformational changes include extracellular receptor regions, and a critical role of the second extracellular loop (E2) for GPCR activation and ligand binding has emerged (5)(6)(7)(8)(9). Rational development of agonistic drugs for GPCR activation requires deeper insight into such conformational changes.…”
mentioning
confidence: 99%